Non-syndromic Oculocutaneous Albinism: Novel Genetic Variants and Clinical Follow Up of a Brazilian Pediatric Cohort - Schidlowski, Laire; Liebert, Fernando; Iankilevich, Pérola Grupenmacher; Rebellato, Priscila Regina Orso; Rocha, Rafaela Andrade; Almeida, Nadia Aparecida Pereira; Jain, Aayushee; Wu, Yiming; Itan, Yuval; Rosati, Roberto; Prando, Carolina (Frontiers in Genetics, 2020)
Oculocutaneous albinism (OCA) is a genetic disorder characterized by skin, hair, and eye hypopigmentation due to a reduction or absence of melanin. Clinical manifestations include vision problems and a high susceptibility to skin cancer. In its non-syndromic form, OCA is associated with six genes and one chromosomal region. Because OCA subtypes are not always clinically distinguishable, molecular analysis has become an important tool for classifying types of OCA, which facilitates genetic counseling and can guide the development of new therapies. We studied eight Brazilian individuals aged 1.5 to 18 years old with clinical diagnosis of OCA. Assessment of ophthalmologic characteristics showed results consistent with albinism, including reduced visual acuity, nystagmus, and loss of stereoscopic vision. We also observed the appearance of the strabismus and changes in static refraction over a two-year period. Dermatologic evaluation showed that no participants had preneoplastic skin lesions, despite half of the participants reporting insufficient knowledge about skin care in albinism. Whole-exome and Sanger sequencing revealed eight different mutations: six in the TYR gene and two in the SLC45A2 gene, of which one was novel and two were described in a population study but were not previously associated with the OCA phenotype. We performed two ophthalmological evaluations, two years apart; and one dermatological evaluation. To the best of our knowledge, this is the first study to perform clinical follow-up and genetic analysis of a Brazilian cohort with albinism. Here, we report three new OCA causing mutations.